Radiographic assessment of hip osteoarthritis progression: impact of reading procedures for longitudinal studies. Issue 6 (1st June 2000) - Auleley, Guy-Robert; Giraudeau, Bruno; Dougados, Maxime; Ravaud, Philippe
Abstract : OBJECTIVE: To compare radiographic reading procedures and evaluate their impact on sample size in hip osteoarthritis (OA) longitudinal studies. METHODS: Pelvic radiographs performed twice, three years apart, in 104 patients with hip OA were read by a single reader using the Kellgren and Lawrence system, joint space narrowing scale, and joint space width (JSW). Reading procedures were ( a ) films read as single radiographs, ( b ) films grouped by patient but read in random order, ( c ) films grouped by patient and chronologically ordered, all with landmarks for JSW measurements, ( d ) films read as single radiographs, without landmarks for JSW measurements. JSW was measured at the narrowest point with a 0.1 mm graduated magnifying glass. RESULTS: More Kellgren and Lawrence or joint space narrowing grades were modified respectively with the single (42% and 37%) than with the paired (32% and 23%) or chronologically ordered (34% and 29%) reading procedures. Variability of JSW progression was principally related to mean progression (88.3%) and landmarks (almost 10%). Standardised response means were −0.71 with the paired reading procedure with landmarks, −0.68 with the single reading procedure with landmarks, −0.65 with the single reading procedure without landmarks. With landmarks, 10% more patients would be needed using single than paired reading. Using single reading, 10% more patients would be needed without landmarks than with landmarks. CONCLUSION: Kellgren and Lawrence grading seems to be influenced by the reading procedure, as is joint space narrowing grading, for assessing hip OA. Paired reading procedure with landmarks for JSW should be recommended in longitudinal studies.